Evolving Roles and Workflows of Creative Practitioners in the Age of Generative AI - Palani, Srishti; Ramos, Gonzalo (Creativity and Cognition, 2024)
Creative practitioners (like designers, software developers, and architects) have started to employ Generative AI models (GenAI) to produce text, images, and assets comparable to those made by people. While HCI research explores specific GenAI models and creativity support tools, little is known about practitioners’ evolving roles and workflows with GenAI models across a project’s stages. This knowledge is key to guide the development of the new generation of Creativity Support Tools. We contribute to this knowledge by employing a triangulated method to capture interviews, videos, and survey responses of creative practitioners reflecting on projects they completed with GenAI. Our observations let us derive a set of factors that capture practitioners’ perceived roles, challenges, benefits, and interaction patterns when creating with GenAI. From these factors, we offer insights and propose design opportunities and priorities that serve to encourage reflection from the wider community of Creativity Support Tools and GenAI stakeholders such as systems creators, researchers, and educators on how to develop systems that meet the needs of creatives in human-centered ways.